PEMANFAATAN TEKNOLOGI DALAM MENINGKATKAN PENJUALAN PADA WARUNG SARIN PAON BALI DI ERA PANDEMI COVID-19 - Pande Ketut Ribek Ribek; Ni Putu Ayu Tirta Yuliasti Yuliasti; I Made Tamba Tamba (LPPM Universitas Mahasaraswati Denpasar, 2023)
ABSTRACT The Covid-19 pandemic has had economic, social and political implications for all countries in the world, including Indonesia. Indonesia, which is dominated by Micro Small and Medium Enterprises (MSMEs) needs to be given special attention to MSMEs which are considered capable of making a major contribution to the country. The digitization of MSMEs is one of the alternatives in Indonesia during the Covid-19 pandemic. The decline in sales during the Covid-19 period has caused business actors to experience a decline in sales and many have closed. This service aims to increase the use of technology in an effort to increase the value of The method used in this research is triangulation, which combines the method of structured interviews, in-depth interviews and observations of SMEs and the technology used. Technology is a science to achieve certain goals practically. The use of technology can improve marketing when done consistently. The results of this activity can make the community and MSMEs able to utilize technology to facilitate effective and efficient marketing. The supporting factors for success in community service activities in developing and increasing income by utilizing technology are the existence of mobile phone facilities that make it easier to create Instagram social media, book stalls, posters for accepting non-cash payments and logos and business business cards, the amount of time the target community has for conduct interviews and implement the program. Keywords: Covid-19, MSME, Technology, Sales Promotion.